The distribution of HBV, HCV and HGV among livers with fulminant hepatic failure of different aetiology - Sergi, Consolato M.; Jundt, Katharina; Seipp, Stefanie; Goeser, Tobias; Theilmann, Lorenz; Otto, Gerd; Otto, Herwart F.; Hofmann, Walter J. (Journal of hepatology, 1998)
Abstract Background/Aims: The aim of the study was to assess the impact factor of HCV and HGV in fulminant hepatic failure.Methods: The 5′-untranslated regions of HCV RNA and HGV RNA and a segment of the core antigen sequence of HBV were amplified after extracting the nucleic acids from snap-frozen tissue aliquots from explanted livers of 26 consecutive patients undergoing orthotopic liver transplantation for fulminant hepatic failure preoperatively diagnosed as either autoimmune (n=2), HAV/HBV (n=8), toxic (n=4) or aetiologically unknown (n=12). Results: HCV RNA was detected in five of 26 (19.2%) livers with fulminant hepatic failure. All five HCV RNA-positive livers belonged to the group of non-toxic, non-autoimmune liver failure (n=20), three of them were found in the group of liver failure with unknown aetiology (n=12) and two in the group of HBV-associated liver failure (n=7), making an HCV incidence of 25%, 25%, and 28.6%, in the different groups, respectively. HGV RNA was detected in 10 of 17 (58.8%) explants and in all four groups of fulminant hepatic failure as defined preoperatively. HBV DNA was identified in six livers of 26 patients (23.1%) with fulminant hepatic failure. Neither HCV RNA nor HBV DNA was detected in the livers of patients with toxic or autoimmune fulminant hepatic failure. Conclusions: These results indicate that HBV and HCV, but not HGV, play an aetiologic role in fulminant hepatic failure. HCV-positive cases were concentrated either in the group of otherwise unexplained fulminant hepatic failure or in the group of HBV fulminant hepatic failure. HGV-positive cases, on the other hand, were found within all four preoperatively defined groups, indicating a role as cofactor rather than as single aetiologic agent.